How to diagnose spondyloarthritis early? Accuracy of peripheral enthesitis detection by power Doppler ultrasonography. Issue 8 (17th May 2011) - D'Agostino, Maria Antonietta; Aegerter, Philippe; Bechara, Karine; Salliot, Carine; Judet, Olivia; Chimenti, Maria Sole; Monnet, Dominique; Le Parc, Jean-Marie; Landais, Paul; Breban, Maxime
Abstract : Objective: Early diagnosis of spondyloarthritis (SpA) is sometimes difficult owing to the lack of reliable diagnostic criteria. The objective of this study was to determine the diagnostic accuracy of detecting enthesitis by power Doppler ultrasonography (PDUS) in patients with suspected SpA. Methods: A prospective single-centre cohort study was performed in patients with symptoms suggestive of SpA (inflammatory back pain, arthritis, enthesitis or dactylitis, HLAB27+ uveitis) who underwent clinical examination, pelvic x-ray, MRI of lumbar spine/sacroiliac joints, HLA-B typing and other tests judged useful for diagnosis. Blinded PDUS examination of seven sites of enthesitis was performed at baseline. The gold standard was the diagnosis made by the referring rheumatologist according to the development of symptoms and findings, blinded to PDUS results, during routine follow-up for up to 2 years. Results: Between November 2002 and October 2004, 118 patients were included in the study. After 2 years a definite diagnosis was retained for 99 patients (51 SpA and 48 non-SpA). PDUS detection of at least one vascularised enthesis provided good predictive value for diagnosing SpA (sensitivity 76.5%; specificity 81.3%; positive likelihood ratio 4.1; OR 14.1; p<0.0001). Vascularised enthesitis detected by PDUS and Amor's criteria were the only independent contributors to a diagnosis of SpA in multivariate logistic regression (c-index=0.87). Alternatively, CART analysis resulted in a highly sensitive and specific diagnostic tree by combining PDUS with Amor's criteria. Conclusions: PDUS appears to be a valuable first-line diagnostic tool to confirm a diagnosis of SpA.